The representation of the kitchen as element of the real estate product in the city of Vitoria between the decades of 1950 to 1970 - Schunig F, Erick Alessandro; Scarin, Paulo Cesar (Geografares, 2017)
This study aims to develop an analysis of the kitchen of the residential apartments in the city of Vitoria, between the 1950s and 1970s, as a space connected to the transformations promoted by capitalism. It was carried out a qualitative survey of advertisements published in a newspaper, as well as the use of authors who approach the relationship between the production of the urban space and the food. From this analysis, it was possible to verify that the transformation in the kitchen is indicative of the way of life established by the Brazilian urbanization during this period.Keywords: Kitchen; Urban space; Advertising.